Model of organizational performance with continuous improvement and technological innovation in micro-enterprises of dairy products - Mármol Cuadrado, Luis Heriberto (2020)
Ecuador – Riobamba city is a cattlee region, where its main source of income is the elaboration of products from fresh milk. Where they have taken 15 micro companies that are dedicated to this area, there are 33 more registered in the MIPRO, which belong to the province of Chimborazo. The purpose of this research is how organizational performance (DO) is directly related to continuous improvement and scientific invention (MC and IC), in which the first must be established in the managers so that the second can be achieved in the processing companies of dairy products. It is concluded that there is indeed a direct influence of the D.O with respect to M.C. and I.C.